2017
DOI: 10.1186/s40538-017-0111-y
|View full text |Cite
|
Sign up to set email alerts
|

Densely rooted rhizosphere hotspots induced around subsurface NH4 +-fertilizer depots: a home for soil PGPMs?

Abstract: Background: Populations of plant growth-promoting microorganisms (PGPMs) inoculated in natural soil typically decline over time due unfavourable biotic and/or abiotic factor(s). Improving subsurface root density may enhance PGPM establishment due to high concentrations of organic nutrients released as root exudates. Placing subsurface root-attracting NH 4 + -fertilizer depots may form such zones of dense localized rooting ("rhizosphere hotspots") that can enhance PGPM survival. Nevertheless, required soil cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…Secretion of phosphohydrolases by soil bacteria (alkaline phosphatases), fungi and plant roots (acid phosphatases) is an important factor mediating the hydrolysis of organic phosphate esters in soils, thereby increasing the plant-availability of phosphate anions in soils (Neumann and Rö mheld, 2002;Khan et al, 2009;Jones and Oburger, 2011). Comparing different fungal and bacterial PGPM strains, Nkebiwe et al (2017) reported particularly high secretory alkaline phosphatase activities in the growth media of the investigated PGPM strain Proradix under conditions of P limitation. Accordingly, Proradix inoculation significantly increased the activity of alkaline phosphatase in the rhizosphere of inoculated maize plants supplied with nitrate fertilization and tested under standard conditions (pH 8.2, 30°C) according to the method of Tabatabai and Bremner (1969), with a similar trend in acid phosphatase (Tab.…”
Section: Effects On Rhizosphere Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Secretion of phosphohydrolases by soil bacteria (alkaline phosphatases), fungi and plant roots (acid phosphatases) is an important factor mediating the hydrolysis of organic phosphate esters in soils, thereby increasing the plant-availability of phosphate anions in soils (Neumann and Rö mheld, 2002;Khan et al, 2009;Jones and Oburger, 2011). Comparing different fungal and bacterial PGPM strains, Nkebiwe et al (2017) reported particularly high secretory alkaline phosphatase activities in the growth media of the investigated PGPM strain Proradix under conditions of P limitation. Accordingly, Proradix inoculation significantly increased the activity of alkaline phosphatase in the rhizosphere of inoculated maize plants supplied with nitrate fertilization and tested under standard conditions (pH 8.2, 30°C) according to the method of Tabatabai and Bremner (1969), with a similar trend in acid phosphatase (Tab.…”
Section: Effects On Rhizosphere Chemistrymentioning
confidence: 99%
“…Rhizosphere soil samples were collected by shaking off root-adhering soil, which was immediately frozen in liquid N and stored at -80°C. Acid and alkaline phosphatase activities were determined based on the p-nitrophenyl phosphate method (Tabatabai and Bremner, 1969) with modifications according to Nkebiwe et al (2017) with 200 mM Naacetate buffer (pH 5.2) for acid phosphatase or 200 mM Naborate buffer (pH 8.2) for alkaline phosphatase. Additional measurements were taken at the rhizosphere pH measured for plants supplied with nitrate or stabilized ammonium fertilization, using 200 mM Na-acetate buffer adjusted to the respective pH values.…”
Section: Rhizosphere Phosphatase Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In an investigation with Bacillus-, Pseudomonas-, and Trichoderma-based inoculants in maize on six different soils in five countries with eight different types of fertilizers based on recycling products from organic and inorganic waste materials, Thonar et al [12] reported superior performance particularly in combination with composted animal manures. Nkebiwe et al [13,14] found beneficial effects by combination of microbial inoculants with placement of stabilized ammonium fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings, we hypothesised that the selection of suitable combinations of microbial inoculants with organic or inorganic fertilizers could be a key factor for the development strategies to improve the fertilizer use efficiency with support of microbial inoculants. Therefore, in this study we compared the performance of greenhouse tomato, supplied with different types of fertilizers (municipal waste compost, poultry manure, rock phosphate, stabilized ammonium) in combination with selected microbial inoculants with proven plant growth-promoting and phosphate-solubilizing properties, pre-selected in the studies of Thonar et al [12] and Nkebiwe et al [13,14]. To also consider the potential impact of different soil properties, the experiments were conducted on two contrasting soils from Ghana with low P availability, and moderately acidic and alkaline pH in face of the significance of soil pH for P fixation in soils.…”
Section: Introductionmentioning
confidence: 99%